Calcination temperature impacting the structure and activity of CuAl catalyst in aqueous glycerol hydrogenolysis to 1,2-propanediol - Mane, Rasika; Potdar, Aparna; Jeon, Yukwon; Rode, Chandrashekhar (Topics in Catalysis, 2024)
This study investigated the impact of calcination temperature on the structural properties of CuAl catalyst which was found to be a robust nano-structured catalyst calcined directly without ramping at 400 °C and performed exceedingly well for aqueous phase hydrogenolysis of glycerol. Various samples of CuAl catalysts were prepared by co-precipitation at Cu: Al molar ratio 1:1 and were calcined at different temperatures (300–1000 °C). The obtained catalysts were reduced at 200 °C before their activity testing for glycerol hydrogenolysis reaction. To correlate the structure-activity, the catalysts were thoroughly characterized by XRD, XPS, BET, TEM, H2-TPR, NH3-TPD, and pyridine FTIR. It was observed that with an increase in calcination temperature from 300 to 700 °C, the glycerol conversion also increased from 47 to 55% with 93% selectivity to 1,2-PDO. The better performance of these catalysts was mainly related to the predominant presence of Brønsted acid sites, an appropriate ratio of the Cu0 to CuAl2O4 + CuO (0.33) and CuAl2O4 to CuO phases (0.35), the existence of Cu2O phase and the smaller Cu0 particle size. It was shown that altering the ramping rate for the calcination temperature of 400 °C impacted the catalytic activity. The CuAl-400 (DC) (direct calcined) catalyst exhibited a maximum glycerol conversion of 60%.